The factors that affect the understanding of reading in elementary school - Nugraha, Susi; Heryanti, Yan Yan; Abidin, Yunus (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
Reading comprehension is one of the four language skills in language learning that must be possessed by every human being, especially students. These skills include speaking, reading, listening, and writing. In the elementary school environment, understanding reading in Indonesian is a challenge for students whose mother tongue is Sundanese. Students with different ethnic backgrounds have distinctive learning styles and language learning strategies. This study used 100 students in class V, consisting of 50 students from SD Negeri Sempur and 50 students from SDN Tanjungsari, as respondents who filled out the questionnaire, which was analyzed using SEM-PLS. This study shows that there are factors that do not affect reading comprehension skills in fifth grade elementary school students at SD Negeri Sempur and SD Negeri I Tanjungsari, namely language aptitude, self-efficacy in language learning, and self-regulation in language, because of the construct path with a T value. Statistics below 1.96 with a p value greater than 0.05 mean that the path is declared to have no significant effect.